Report on the International Symposium on Bioproducts Processing - Hashim, M.A.; Sastry, C.A.; Ibrahim, Shaliza; Vikineswary, S.; Yap, S.Y. (Malaysian Society for Molecular Biology and Biotechnology, 1994)
The Institute of Advanced Studies (IPT), University of Malaya convened an International Symposium from the 4-7 January, 1994. It was the first of its kind in the region. The Ministry of Science, Technology and Environment of Malaysia, The Institution of Chemical Engineers-U.K., The Institution of Chemical Engineers-Australia and The Institution of Engineers Malaysia co-sponsored the Symposium. Financial aid was also received from some 25 different agencies. 180 participants from 18 countries including private entrepreneurs from the U.S.A. and New Zealand attended the conference. In all, 76 papers encompassing various related topics were presented, including 16 invited papers from eminent international scientists and engineers. The highlights of the symposium are presented below.